UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR PADA MATA PELAJARAN IPAS DENGAN METODE GROUP INVESTIGATION PADA SISWA KELAS IV MI IMAM PURO BRENGGONG - Ananda Cahya Trisna Putri; Nur Ngazizah; Titi Anjarini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to: 1) Determine the application of the GI method in science. 2) Determine the increase in student engagement in science. 3) Determine the improvement in student learning outcomes in science. This study used a classroom action research (CAR) approach, implemented in two cycles, each consisting of planning, implementation, observation, and reflection, using the Group Investigation method. The study subjects were 20 students, consisting of 10 boys and 10 girls. Data collection techniques included observation, interviews, tests, and documentation. Data analysis was conducted qualitatively and quantitatively. The results showed that: 1) The implementation of the GI method was carried out through six stages: grouping, planning, investigation, organizing, presenting, and evaluation. 2) The increase in student engagement was evident from observations: 36% in the pre-cycle, increasing to 58% in the first meeting of cycle I and 65% in the second meeting of cycle I, reaching 78% in the first meeting of cycle II and 93% in the second meeting of cycle II. The category of student activity developed from “less active” to “quite active”, to “very active”. 3) Student learning outcomes also experienced a significant increase. With an average score of 69 in the pre-cycle, 74 in cycle I, and 88 in cycle II. The percentage of classical completion in cycle II reached 95%, exceeding the learning objective achievement criteria (KKTP). Thus, the application of the Group Investigation method has proven effective in increasing student activity and learning outcomes in the subject of science.